Childhood environmental harshness and unpredictability negatively predict eHealth literacy through fast life-history strategy - Feng, Wenfei; Zhang, Jinguang (Frontiers in Psychology, 2023)
Background: eHealth literacy-the ability to obtain, understand, evaluate, and use health information from the Internet-is important to maintaining and improving personal health. Prior research found that people differ notably in the levels of eHealth literacy, and this study tests a theoretical account of some of those individual differences. Drawing on life history theory, we propose that low eHealth literacy is partly the outcome of people adopting a resource-allocation strategy emphasizing early and fast reproduction, namely, a fast life-history strategy.We conducted a cross-sectional survey study (N = 1,036) that measured Chinese adult respondents' eHealth literacy, childhood environmental harshness and unpredictability, and fast lifehistory strategy. Covariates included health-information seeking online, self-rated health, sex, age, education level, and monthly income.Results: Supporting a life-history explanation of eHealth literacy, childhood environmental harshness and unpredictability negatively predicted eHealth literacy through fast life-history strategy and mainly the insight-planning-control dimension of it. Harshness, not unpredictability, also directly and negatively predicted eHealth literacy after fast life-history strategy was controlled for.Our findings suggest that the psychological mechanisms associated with human lifehistory strategies produce at least some of the individual differences in levels of eHealth literacy, including those related to neuroticism, socioeconomic status, self-rated health and social capital. Thus, a possible way to increase future generation's eHealth literacy and thereby their health is to reduce the harshness and unpredictability of the environment in which they grow up, thereby making them more likely to adopt a relatively slow life-history in their adulthood.